2023
DOI: 10.1109/jiot.2023.3243207
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on IoT Positioning Leveraging LPWAN, GNSS, and LEO-PNT

Abstract: Location data is an important piece of information in many Internet of Things (IoT) applications. Global Navigation Satellite Systems (GNSS) have been established as the standard for large-scale localization. However, the rapidly increasing need to locate IoT devices in recent years has exposed several shortcomings of traditional GNSS approaches. These limitations include the weak signal propagation in indoor and dense environments, the inability to calculate or obtain a location remotely, and a high energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The specific simulation parameters are listed in Table I. To ensure the execution of the algorithm, we assume that our system is capable of compensating for Doppler effects and accurately predicting the positions of satellites [19]. For the MARL parameters, we set that the reply memory size is |M| = 16, the mini-batch size is 4, and the maximum training episode is T max = 6000.…”
Section: A Simulation Settingsmentioning
confidence: 99%
“…The specific simulation parameters are listed in Table I. To ensure the execution of the algorithm, we assume that our system is capable of compensating for Doppler effects and accurately predicting the positions of satellites [19]. For the MARL parameters, we set that the reply memory size is |M| = 16, the mini-batch size is 4, and the maximum training episode is T max = 6000.…”
Section: A Simulation Settingsmentioning
confidence: 99%
“…In addition, configuring LEO satellites to rebroadcast GNSS-like signals on other frequency bands can help these signals mitigate most atmospheric effects. Furthermore, LEO's higher signal strength can increase the availability of these signals in hard-to-reach places [4,[10][11][12][13]. Studies have also shown a significant improvement in positioning accuracy for users that receive their signals from LEO-augmented GNSS satellites [14,15].…”
Section: Introduction and Motivation 1leo-pnt Versus Gnssmentioning
confidence: 99%
“…Standalone positioning services reach meter-level accuracies under open sky conditions. This has made GNSS the de-facto standard for many positioning applications [93]. Although GNSS can provide reliable and accurate location data anywhere globally, it is not the best solution for all localization problems.…”
mentioning
confidence: 99%
“…On the other hand, GNSS technology has relatively high energy consumption in its typical use case, which aligns poorly with the stringent constraints of batterypowered devices [21]. Therefore, more energy-efficient positioning alternatives like terrestrial Low Power Wide Area Networks (LPWANs), such as LoRaWAN and Narrow-band IoT (NB-IoT), are gaining increasing popularity [93]. Also, in order to mitigate these two challenges, GNSS has been integrated with other technologies such as Wi-Fi, Bluetooth Low Energy (BLE), or Inertial Navigation Systems (INS).…”
mentioning
confidence: 99%
See 1 more Smart Citation